CRISPR/Cas9: an advanced platform for root and tuber crops improvement - Divya, K.; Thangaraj, Makeshkumar; Krishna Radhika, N. (Frontiers in Genome Editing, 2024)
Root and tuber crops (RTC), including cassava, potato, sweet potato, and yams, principally function as staple crops for a considerable fraction of the world population, in addition to their diverse applications in nutrition, industry, and bio-energy sectors. Even then, RTC are under-utilized group considering its potential as an industrial raw material. Complexities in conventional RTC improvement programs curb the extensive exploitation of the potentials of this group of crop species for food, energy production, value addition, and sustainable development. Now, with the advent of whole genome sequencing, sufficient sequence data is available for cassava, sweet potato, and potato. These genomic resources provide enormous scope for improvement of tuber crops, to make them better suited for agronomic and industrial applications. There has been remarkable progress in RTC improvement through the deployment of new strategies like gene editing over the last decade. This review brings out the major areas where CRISPR/Cas technology has improved the tuber crops. Strategies for genetic transformation of RTC with CRISPR/Cas9 construct and regeneration of edited lines and the bottlenecks encountered in their establishment are also discussed.Certain attributes of tuber crops requiring focus in future research along with putative editing targets are also indicated. Altogether, this review provides a comprehensive account of developments achieved, future lines of research, bottlenecks, and major experimental concerns regarding the establishment of CRISPR/Cas9-based gene editing in RTC.